B cells facilitate platelet production mediated by cytokines in patients with essential thrombocythaemia - Liu, Chuan-Chuan; Wang, Shu-Ching; Kao, Chen-Wei; Hsieh, Ruey-Kuen; Chang, Ming-Chih; Chang, Yi-Fang; Lim, Ken-Hong; Chen, Caleb Gonshen (Thrombosis and Haemostasis, 2014)
We investigated the role of activated B cells in thrombopoiesis through the production of interleukin (IL)-1beta and IL-6 in patients with essential thrombocythaemia. The number of B cells did not differ between essential thrombocythaemia patients, irrespective of the presence of Janus activated kinase-2 V617F mutation or wild type, and age-matched healthy adults. However, the number of IL-1beta/IL- 6-producing B cells was significantly higher in essential thrombocythaemia patients than that in healthy controls. The relatively high level of IL-1beta/IL-6 production by B cells was associated with serum B cell-activating factor and expression of Toll-like receptor 4 on B cells. A high level of B cell-activating factor was present in essential thrombocythaemia patients with both Janus activated kinase-2 genotypes. Incubation with B cell-activating factor enhanced the expression of Toll-like receptor 4 on B cells. IL-1beta and IL-6 production was not stimulated by B cell-activating factor alone; Toll-like receptor 4 was activated by lipopolysaccharide or patients’ sera to produce IL-1beta and IL-6 in B cells. Moreover, essential thrombocythaemia patient B cells facilitated megakaryocyte differentiation when co-cultured with CD34+ haematopoietic stem cells. Antibody neutralisation of IL-1beta and IL-6 attenuated megakaryocyte differentiation. These data suggest that B cells play a crucial role in thrombopoiesis in essential thrombocythaemia patients.
Keywords: Essential thrombocythaemia; B cell-activating factor; TLR4; IL-1beta; IL-6